The right stuff; realizing the potential for enhanced biomass production in microalgae - Subramanian, Sowmya; Sayre, Richard T (Frontiers in Energy Research, 2022)
There is growing evidence that eukaryotic microalgae can become a more sustainable and profitable alternative than terrestrial crops to produce feed, fuels, and valuable coproducts. The major factor driving progress in algal biomass production is the potential of microalgae to produce substantially greater biomass per unit land area than terrestrial crops. To be financially feasible, however, current algal biomass yields must be increased. Given the fact that algal biomass production is in its infancy there exist multiple opportunities to improve biomass yields. For example, recent bioprospecting efforts have led to the identification of new microalgal strains having biomass yields that compete economically with plant biomass. Substantial increases in biomass yields have also been achieved using advanced genetic engineering approaches. Targeted improvements in photosynthetic efficiency have led to three-fold increases in algal biomass yields. One genetic tool that has seen limited application for algal biomass enhancement is advanced breeding genetics. The greater availability of algal genomes and recent advancements in breeding algae will further accelerate yield improvements. Genetic engineering strategies to increase biomass production will also be assisted by transcriptomic and metabolomic studies that help identify metabolic constraints that limit biomass production. In this review we assess some of the recent advances in algal strain selection, directed evolution, genetic engineering and molecular-assisted breeding that offer the potential for increased algal biomass production.